Debates contemporáneos en derecho de familias, de infancias y de adolescencias - Ariza Sosa, Gladys Rocío; Agudelo Galeano, Juan Jacobo; Saldarriaga Grisales, Dora Cecilia; Vanegas Arango, Anyela Alejandra; Saldarriaga Quintero, Luisa Alejandra; Cardona Zuleta, Elvigia; Pabón Mantilla, Ana Patricia; Aguirre Román, Javier Orlando; Vásquez Santamaría, Jorge Eduardo; Restrepo Múnera, Carolina; Castro Restrepo, María Clara; Estrada Jaramillo, Lina Marcela; et al. (Universidad Católica Luis Amigó, 2022)
This work results from the call for proposals “Contemporary debates on family, childhood and adolescent law. Challenges and realities” carried out by the Luis Amigó Catholic University. It consists of a series of contributions from academics and professionals who seek, from an interdisciplinary perspective, to broaden the debate in family, childhood, and adolescent law. The reader will find reflections on the transformation in affective relationships between couples in Colombia, the recognition of successor rights to foster children, the right to probation in family law from a gender perspective, and the importance of citizenship education of children and adolescents. Likewise, the reader will be able to delve into issues of social and environmental relevance, such as the drama of migrant children, the armed conflict and forced recruitment, and the active role of children and adolescents in the fight against climate change and conservation of the Amazon.